Operations and Similarity Measures Between (m,n)-Fuzzy Sets - Thakur, Samajh Singh; Banafar, Anita Singh; Thakur, Mahima; Pandey Bajpai, Jyoti; Prasad, Archana Kumari (IndoMS, 2024)
Recently Jun and Hur proposed (m, n)-fuzzy sets which can handle vagueness and uncertainty in information very efficiently in the process of solving complex problems. They defined basic operations over (m, n)-fuzzy sets. The present paper created some new operations over this super class of fuzzy sets and established many theorems related to the their properties. Further some distance and similarity measures of (m, n)-fuzzy sets are proposed and their properties are examined. Moreover, the proposed similarity measures are applied to the problem of pattern recognition.